Giant Pediatric Dural Arteriovenous Fistula Management Using a Combined Operative Approach in a Hybrid Neuroendovascular Surgery Suite: Technical Nuances and Review of Literature. Issue 4 (12th April 2023) - Saway, Brian Fabian; Porto, Guilherme B. F.; Sattur, Mithun G.; Domingo, Ricardo A.; Triano, Matthew; Al Kasab, Sami; Eskandari, Ramin; Lena, Jonathan R.
Abstract : BACKGROUND: Pediatric intracranial dural arteriovenous fistulas (dAVFs) are rare, complex entities usually presenting with macrocephaly from increased intracranial pressures at a young age. In the setting of a symptomatic intracranial dAVF that has undergone multiple endovascular treatments with subsequent recurrence or failed embolization attempts, the intracranial venous system can become inaccessible by traditional transvenous and transarterial routes. Direct puncture of the venous sinus for endovascular access after surgical exposure is a viable option. OBJECTIVE: To describe the technical nuances and available literature for direct puncture of the venous sinus for endovascular access in a pediatric patient with dAVF. METHODS: The clinical characteristics were reviewed and reported for a patient who underwent direct puncture of the venous sinus for endovascular access. In addition, a literature review was conducted for relevant literature pertaining to this technique and its associated indications, outcomes, and complications. RESULTS: Only 2 other reports of direct puncture of venous sinus for endovascular access after surgical exposure were found in the literature. Our patient achieved a favorable outcome with complete dAVF obliteration. CONCLUSION: Direct puncture of the venous sinus for endovascular access after surgical exposure for complex dAVFs that are inaccessible by transvenous or transarterial routes is a practical and safe approach to intracranial venous access that should be part of the vascular neurosurgeon's arsenal. Abstract :